2020
DOI: 10.36941/jesr-2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Bullying in Schools: The Viewpoint of School Directors. Suggestions for Mitigating the Phenomenon - A Case Study of the District of Tirana

Abstract: One of the most important institutions which affects the development and education of individuals in society is the school. The territory of schools needs to be safe from any form of violence, including bullying. Bullying in itself is a phenomenon that is defined as a behavior which occurs when an individual or a certain group of individuals, taking advantage of their power or authority, seek to impose, persecute, abuse, or intimidate the weaker ones repeatedly (Dema, 2007). Given that various studies consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Gómez-Ortiz et al (2018) said parenting in the family could be the preventive element for high school students to be involved with cyberbullying. According to Kallciu et al (2020), a family's economic status situation could be the element in the emergence of bullying. In addition, Rakic et al (2021) informed that family characteristics such as the family's affluence status, the father's occupation, communication with the father, and the family's support could be the factors that could help raise awareness in getting rid of cyberbully.…”
Section: Theme 3: Family Elementmentioning
confidence: 99%
“…Gómez-Ortiz et al (2018) said parenting in the family could be the preventive element for high school students to be involved with cyberbullying. According to Kallciu et al (2020), a family's economic status situation could be the element in the emergence of bullying. In addition, Rakic et al (2021) informed that family characteristics such as the family's affluence status, the father's occupation, communication with the father, and the family's support could be the factors that could help raise awareness in getting rid of cyberbully.…”
Section: Theme 3: Family Elementmentioning
confidence: 99%
“…School bullying has become a common type of violence in modern society and is becoming more universally recognised as a significant global issue (Ahmed, et al, 2022;O'Higgins et al, 2022). Education policymakers around the world are becoming more concerned about bullying (Nansel et al, 2004;Rigby, 2007;Rivara et al, 2016), despite the fact that the prevalence of bullying has been shown to differ greatly between countries (Craig et al, 2009;Kallciu et al, 2020;Nansel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%